The Monosyllable Imitation Test for Toddlers: influence of stimulus characteristics on imitation, compliance and diagnostic accuracy. Issue 1 (13th April 2016) - Hodges, Rosemary; Munro, Natalie; Baker, Elise; McGregor, Karla; Heard, Rob
Abstract: Background: Although verbal imitation can provide a valuable window into the developing language abilities of toddlers, some toddlers find verbal imitation challenging and will not comply with tests that involve elicited verbal imitation. The characteristics of stimuli that are offered to toddlers for imitation may influence how easy or hard it is for them to imitate. This study presents a new test of elicited imitation—the Monosyllable Imitation Test for Toddlers (MITT)—comprising stimuli of varying characteristics and test features designed to optimize compliance. Aims: To investigate whether the stimulus characteristics of neighbourhood density and consonant complexity have independent and/or convergent influences on imitation accuracy; and to examine non‐compliance rates and diagnostic accuracy of the MITT and an existing test, the Test of Early Nonword Repetition (TENR) (Stokes and Klee 2009a). Methods & Procedures: Fifty‐two toddlers (25–35 months) participated. Twenty‐six had typically developing language (TDs) and 26 were defined as late talkers (LTs) based on parent‐reported vocabulary. The MITT stimuli were created by manipulating both neighbourhood density (dense or sparse) and consonant complexity (early‐ or late‐developing initial consonant). The MITT was designed to maximize compliance by: (1) using eight monosyllabic stimuli, (2) providing three exposures to stimuli and (3) embedding imitation in a motivating context: a computer animation with reasons for imitation. Outcomes & Results: Stimulus characteristics influenced imitation accuracy in TDs and LTs. For TDs, neighbourhood density had an independent influence, whereas for LTs consonant complexity had an independent influence. These characteristics also had convergent influences. For TDs, stimuli were all equally easy to imitate, except those that were both sparse and contained a late‐developing consonant which were harder to imitate. For LTs, stimuli that were both dense and contained an early‐developing consonant were easier to imitate than any other stimuli. Two LTs and no TDs were non‐compliant with the MITT. With the TENR, five LTs and two TDs were non‐compliant. The MITT and TENR yielded similar levels of diagnostic sensitivity, but the TENR offered higher specificity rates. Subsets of stimuli from the MITT and the TENR also showed diagnostic promise when explored post‐hoc. Conclusions & Implications: Stimulus characteristics converge to influence imitation accuracy in both TD and LT toddlers and therefore should be considered when designing stimuli. The MITT resulted in better compliance than the TENR, but the TENR offered higher specificity. Insights about late talking, elicited imitation and speech production capabilities are discussed.